A remarkable new species of Qualea (Vochysiaceae) from Piauí state, Brazil - Shimizu, Gustavo Hiroaki; Gonçalves, Deise Josely Pereira; França, Flávio; Simões, André Olmos; Yamamoto, Kikyo (Phytotaxa, 2016)
Qualea insignis, a new species of Vochysiaceae endemic to the Serra das Confusões area, Piauí state, Brazil, is here described and illustrated. The species is placed in Qualea sect. Costatifolium, due to the number of secondary veins/cm and the inflorescence architecture. A comparison with Q. grandiflora and Q. parviflora, the other species of the genus occurring in the Caatinga, is also provided.